2000
DOI: 10.1111/j.1469-8749.2000.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of ideomotor praxis representation

Abstract: To create a short screening instrument to investigate the development of ideomotor praxis representation (IPR), 357 normally developing children between the ages of 21/2 and 91/2 years were investigated. The IPR screening consisted of six mimed actions which had to be performed on verbal request. The greatest change in the representational style is the transition from performing the action using the body as the object to performing with an imaginary object (i.e. symbolic representation). This transition sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…These findings are consistent with a large body of research demonstrating a systematic developmental progression in symbolic gesture production during early childhood (Dewey, 1993;Kaplan, 1968;Kools & Tweedie, 1975;Njiokiktjien et al, 2000;Overton & Jackson, 1973). Our results suggest that non-symbolic gesture imitation may develop along a similar orderly continuum.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with a large body of research demonstrating a systematic developmental progression in symbolic gesture production during early childhood (Dewey, 1993;Kaplan, 1968;Kools & Tweedie, 1975;Njiokiktjien et al, 2000;Overton & Jackson, 1973). Our results suggest that non-symbolic gesture imitation may develop along a similar orderly continuum.…”
Section: Discussionsupporting
confidence: 93%
“…The sex difference we observed appears to be established from an early age. This contrasts with previous studies that reported no sex difference in children's gesture production skills (Cermak et al, 1990;Njiokiktjien et al, 2000;Overton & Jackson, 1973). Those studies, however, employed less refined scoring methods than the one used here, in that they did not separate praxic (motor selection) from nonpraxic (motor execution) errors.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In a group of typically developing children, Njiokiktjien and colleagues found a constant maturation of execution precision of imitation and pantomime performances until the age of 6 years. 27 The preference of a body-part-as-an-object grip instead of accurate symbolic grip is also typical for younger children. Typically developing 4-year-old children mime on verbal command a transitive gesture with a body-part-as-an-object grip.…”
Section: Discussionmentioning
confidence: 99%
“…Njiokiktjien et al 19. examined healthy children to develop a screening instrument for the development of “ideomotor praxis representation.” They defined ideomotor praxis as “the ideation, organization, and execution of single acts (e.g.…”
Section: The Normal Development Of Praxismentioning
confidence: 99%